2014
DOI: 10.1016/j.jiac.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of aerosolized liposomal amphotericin B against murine invasive pulmonary mucormycosis

Abstract: Invasive pulmonary mucormycosis is a life-threatening fungal infection encountered in immunocompromised patients. An intravenous high-dose lipid formulation of amphotericin B, such as liposomal amphotericin B (L-AMB), is the recommended treatment. The efficacy of inhaled L-AMB against mucormycosis has not been evaluated.We evaluated the efficacy of inhaled aerosolized L-AMB in murine invasive pulmonary mucormycosis. ICR female mice were immunosuppressed with cortisone acetate and cyclophosphamide and challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…n-AmB prophylaxis have been studied in animal models of aspergillosis, on rats [ 35 , 37 , 56 , 88 , 89 ], mice [ 36 ], and guinea pigs [ 90 ]. The only study assessing n-AmB for mucormycosis prophylaxis showed negative results with n-L-AmB [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…n-AmB prophylaxis have been studied in animal models of aspergillosis, on rats [ 35 , 37 , 56 , 88 , 89 ], mice [ 36 ], and guinea pigs [ 90 ]. The only study assessing n-AmB for mucormycosis prophylaxis showed negative results with n-L-AmB [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…The dose of NAB for the treatment of pulmonary mucormycosis remains unclear 14 . Most data are from case reports where both lipid and non‐lipid formulations of amphotericin B have been used in varying doses 11,12,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, all the available amphotericin B formulations achieve therapeutic concentrations in the alveolar lining fluid but negligible systemic levels, thereby avoiding serious systemic adverse events 10,13 . Data from murine models and a few case reports suggest a possible role of NAB in managing PM 14,15 . We hypothesized that combining inhalational and intravenous amphotericin B would result in better outcomes than intravenous amphotericin B alone in PM.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only one experimental study was dedicated to prophylaxis with L-AmB treatment (30). This study used nebulized L-AmB in a mouse model of R. oryzae pulmonary infection.…”
Section: Lung Decolonization To Prevent Mucormycosismentioning
confidence: 99%